O discurso da mídia impressa do Ceará sobre a carcinicultura entre 2002 e 2005 - Crispim, Maristela Machado (2008)
The Ceará’s press media discourse about shrimp aquaculture, between 2002 and 2005, is the principal theme of this research, which approach is the 43 newspaper reports titles about shrimp aquaculture, published on “Diário do Nordeste” and “O Povo” newspapers. To do it, at first, a research on shrimp aquaculture activity at Ceará State was made, utilizing the most important studies published about it. On this reconstruction, are considered sustainability; Economy, Ecology and Entropy Law concepts and its implications on socio-environmental questions; the mangrove importance; the shrimp aquaculture development on Ceará State; and, also, some of the principals impacts related to the activity, as the destruction and / or interference on the mangrove ecosystem balance. It’s also treated the environmental news construction, emphasizing not only the mediation activity between the occurrence and the reader. For this, reference researches from the journalism theories are emphasized, including the Newsmaking, which concerns to de relevance and noticiability criteria, the news-value of selection and construction, and the reading contract. The ethic and the journalism on environmental questions are also focused; considering the challenge of being journalist incorporating the complex thinking virtues on the reality construction work. To the comprehension of the press media discourse, is utilized the Discourse Analysis’ theory methodological tools, beginning from the necessity to join language [text] and ideology [context], to the comprehension of sense construction, with it’s enunciatively strategies. The objective is verify how, through the titles, on the various parts of the two newspapers, the theme was treated on the emphasized period of the analysis – considering the text and the context of the newspaper reports production – to show how the Ceará’s shrimp aquaculture discourse is constructed to the readers.